FORCA DA VIDA (A) - EISNER, WILL, 1917-2005; MAIA, MARQUITO (SAO PAULO DEVIR, 2007)
.
PORTUGUES
TRADUCAO DE: A LIFE FORCE. BIOGRAFIA DO AUTOR.
Keywords: ESTADOS UNIDOS; FICCAO; HQ; HISTORIAS EM QUADRINHOS; GRAPHIC NOVELS; LIVRO